Combined high‐fat‐resveratrol diet and RIP140 knockout mice reveal a novel relationship between elevated bone mitochondrial content and compromised bone microarchitecture, bone mineral mass, and bone strength in the tibia. Issue 9 (21st April 2016) - Miotto, Paula M.; Frendo‐Cumbo, Scott; Sacco, Sandra M.; Wright, David C.; Ward, Wendy E.; Holloway, Graham P.
Abstract : We evaluate the effects of a combined high fat‐resveratrol (HF‐RSV) diet on bone mitochondrial content and bone health. Our results demonstrate that HF‐RSV results in increased bone mitochondrial content, which is associated with greater markers of bone resorption and weaker bone. We further establish a relationship between elevated mitochondrial content and impaired bone health by using RIP140 knockout mice. Similar to HF‐RSV mice, RIP140 KO mice have increased bone resorption and impaired bone health – establishing a negative association between excess bone mitochondrial content and bone health. Abstract : Scope: While resveratrol (RSV) is associated with the prevention of high‐fat (HF) diet‐induced insulin resistance, the effects on bone health combined with an HF‐diet is unknown. Therefore, we determined the effect of RSV on bone microarchitecture in the presence of an HF‐diet, while also elucidating molecular adaptations within bone that could contribute to bone health status. Methods and results: Male C57BL6 mice were provided control (10% fat) or HF‐diet (60% fat) in the presence or absence of RSV for 12 weeks. While RSV prevented HF diet‐induced glucose intolerance, HF‐RSV compromised tibial microarchitecture, mineral mass, and strength. The compromised outcomes following HF‐RSV corresponded with higher markers of osteoclast‐activation and bone‐resorption (decreased OPG/RANKL ratio; increased cathepsin K), as well as higher markers of tibial mitochondrial content. A molecular model of elevated mitochondrial content (RIP140 knock out (KO) mice) was utilized to determine proof‐of‐principle that increasing mitochondrial content coincides with decrements in bone health. RIP140 KO mice displayed higher markers of mitochondrial content, and similar to HF‐RSV, had compromised bone microarchitecture, lower BMD/strength, and higher markers of osteoclast‐activation/bone‐resorption. Conclusion: These data show that in the presence of an HF‐diet, RSV negatively alters bone health, a process associated with increased mitochondrial content and markers of bone resorption.